Beach-Dune System Morphodynamics - D'Alessandro, Felice; Tomasicchio, Giuseppe Roberto; Frega, Ferdinando (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Coastal dunes are known for their functions in ecological systems in addition to their aesthetic qualities, providing a highly valuable and unique habitat due to their biodiversity of flora and fauna. They also represent the boundary between land and sea, acting as a protective natural barrier against flooding due to storm surges and wave action. Beach-dune systems are highly dynamic features whose evolution is primarily determined by the mutual and complex exchange of sand through hydrodynamic and eolian processes. The sustainable and resilient conservation of beach-dune (eco)systems in a changing climate requires important insights from multidisciplinary studies and approaches. Toward this vision, this Special Issue is dedicated to collecting original scientific contributions based on field observations, laboratory experiments, and/or numerical models.